Right Ventricular Myocardial Infarction as an Independent Predictor of Prognosis in Acute Inferior Myocardial Infarction (TAJ: Journal of Teachers Association, 2018)
Background: Acute inferior myocardial Infarction frequently involves the right ventricle and associated with significant morbidity and mortality. We hypothesized that right ventricular involvement may affect the prognosis of patients with inferior myocardial infarctions.Methodology: In 100 consecutive patients admitted to the hospital with acute inferior myocardial infarction, we assessed the incidence and prognostic factors for in-hospital outcome. RVMI (Right ventricular myocardial infarction) was diagnosed by ≥1mm ST elevation in lead V4R in right sided electrocardiogram.Result: RVMI was found in 31(31%) of patients of acute inferior myocardial infarctions. Major complications as hypotension and cardiogenic shock occurred in 96.7% and 64.5% patients respectively and in-hospital mortality was 41.9%. Whereas major complications as hypotension and cardiogenic shock occurred in 10.1% and 2.8% patients respectively and in hospital mortality was 2.8% of patients without right ventricular infarction among the inferior myocardial infarction. Multiple logistic regression analysis showed right ventricular infarction to be independent of and superior to all other clinical variables available on admission for the prediction of in hospital mortality (relative risk 88.37 percent, 95% confidence interval 7.33 to 1064.80; p=0.000) and major complications as hypotension (relative risk 394.22, 95% confidence interval 32.04 to 4849.07; p=0.000) and cardiogenic shock (relative risk 272.36, 95% confidence interval, 16.38 to 4526.35; p=0.000).Conclusion: RVMI commonly occurs in inferior myocardial infarction. It is a strong and independent predictor of major complications and in-hospital mortality. Early detection and appropriate monitoring can reduce its high mortality rate.TAJ 2013; 26: 8-13